The Brain in Context: A Scoping Review and Concept Definition of Neuro-Informed Policy and Practice - Sally Staton; Laetitia Coles; George Normore; Charlotte Casey; Bonnie Searle; Sandy Houen; Azhar Potia; Rebecca Crompton; Deborah Long; Michael Hogan; Karen Thorpe (Brain Sciences)
Background/objectives: Among the developmental sciences, discovery in neuroscience has underpinned research innovations and made a significant contribution to knowledge translation. With the growth of neuroscience discovery, policymakers and practitioner workforces have adopted ‘neuro-informed’ in decisions targeting the delivery of human, social, and economic wellbeing. Methods: In this scoping review, we examined the use and conceptualization of neuro-informed policy and practice (NPP) over the last two decades. We aim to establish a working definition of NPP and identify the key knowledge bases underpinning the application of NPP, with a specific focus on children and young people. Results: A total of 116 publications related to NPP were identified across academic and policy sources. Publications derived from diverse fields (e.g., psychology, social policy, medicine, urban planning). Health and Education were the most common target areas for NPP; however, applications of NPP to social services, law, and physical environments were also identified. Despite the growth in NPP, concept definitions of NPP were limited and primarily tautological. A four-stage process of concept definition was used to develop a working definition of NPP applicable to different systems, workforces, and contexts. By applying content analysis, 12 distinct knowledge bases underpinning NPP were identified. Conclusion: Our scoping review highlights the importance of defining the concept of neuro-informed policy and practice, extending beyond the brain or individual in isolation to include consideration of the brain in context.